2005
DOI: 10.1111/j.1939-1676.2005.tb02769.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Survival Times of Dogs Treated with Mitotane or Trilostane for Pituitary-Dependent Hyperadrenocorticism

Abstract: The survival times of 148 dogs treated for pituitary-dependent hyperadrenocorticism were studied using clinical records from 3 UK veterinary centers between 1998 and 2003. Of these animals, 123 (83.1%) were treated with trilostane, while 25 (16.9%) were treated with mitotane. Treatment groups were compared using t-tests and analysis of variance (or their nonparametric equivalents) and chi-square tests. Survival data were analyzed using Kaplan-Meier survival plots and Cox proportional hazard methods. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 14 publications
9
27
2
3
Order By: Relevance
“…36 Concerning age, other studies that included dogs treated with trilostane or mitotane have reported similar results. 33,35 In contrast, age was not reported to be associated with survival in another study that included dogs treated with trilostane, and our results are consistent with theirs. 32 The reason for this difference is not clear.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…36 Concerning age, other studies that included dogs treated with trilostane or mitotane have reported similar results. 33,35 In contrast, age was not reported to be associated with survival in another study that included dogs treated with trilostane, and our results are consistent with theirs. 32 The reason for this difference is not clear.…”
Section: Discussionsupporting
confidence: 91%
“…days. [32][33][34][35][36] In our study, median survival time was not reached for the trilostane group during the study period. Because the trilostane group in our study included fewer cases (n = 17) with a small number of cases at risk after 2 years, we conducted survival analysis at 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no studies demonstrating good correlation between a systematic evaluation of owners’ observations of clinical control and the post-ACTH stimulation cortisol. There is also a lack of consensus regarding the target post-ACTH stimulation cortisol concentration in trilostane-treated dogs with values varying from 15 to 250 nmol/l used to define good clinical control (Neiger and others 2002, Ruckstuhl and others 2002, Braddock and others 2003, Wenger and others 2004, Barker and others 2005, Galac and others 2010, Ramsey 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the clinical features of canine hyperadrenocorticism in the UK (Neiger et al 2002, Barker et al . 2005, Kenefick & Neiger 2008, Helm et al 2011, Augusto et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%